Assessing the carbon footprint of tourism businesses using environmentally extended input-output analysis. Issue 1 (9th December 2021) - Demeter, Csilla; Lin, Pei-Chun; Sun, Ya-Yen; Dolnicar, Sara
Abstract: The tourism industry contributes eight percent to global carbon emissions, directly and indirectly. Indirect carbon emissions are often neglected because they are difficult to calculate. The traditional approach to calculating indirect emissions – Life Cycle Assessment – is expensive and requires an expert data analyst. We introduce an alternative approach, the Environmentally Extended Input-Output Analysis. We show how this approach – currently used at macro-level to estimate carbon emissions at national or regional level – can be applied to the business level using carbon emissions generated by one hotel room clean as an example. Our comparative analysis shows that Environmentally Extended Input-Output Analysis leads to similar results as Life Cycle Assessment, while being substantially cheaper and more user-friendly. Environmentally Extended Input-Output Analysis, we conclude, enables tourism businesses to estimate the indirect carbon emissions of their operations, which is the key to identifying target areas for improvement.